The Mitigating Circumstances System and its Impact on the Assessment of Punishment and Compensation: A Comparative Study between Islamic Jurisprudence and Jordanian Law - Karabsheh, Abdel-Kareem Ottallah (Journal of Cultural Analysis and Social Change, 2025)
The circumstances of crime are among the innovations of criminal jurisprudence. Its importance lies in the fact that it is one of the main determinants of the type and extent of punishment, researches proved that the circumstances surrounding the crime have a major role in determining the gravity of the crime and the seriousness of the offender. A person who has become accustomed to crime and repeated this cannot be treated as an accidental criminal. The Islamic Sharia was keen to distinguish between the two, and it was tightened with the first and permitted the judge to reduce the second if the judge considers that the interest of the society lies in that. Likewise, laws did, including the Jordanian Penal Code, which adopted a system of mitigating circumstances in the materials with the numbers (95) to (100).